Preliminary study of the impact of pig or goat manure fertilization of a meadow on oribatid mites - Seniczak, Anna; Seniczak, Stanisław; Szczukowska, Hanna; Graczyk, Radomir; Bukowski, Grzegorz (Biological Letters, 2017)
We investigated the impact of pig or goat manure fertilization of a meadow with doses of 80 kg N ha−1, 140 kg N ha−1, and 200 kg N ha−1 (plots 1-6) on oribatid mites. A control plot (0) was left unfertilized. The manure was applied to the meadow in the early spring of 2012, and soil samples were collected in the spring of 2012 and 2013. In total, 6053 oribatid mites were examined, including 1163 juveniles. The effect of fertilizing on the Oribatida depended on the dose of manure, but not on its type. A low dose of pig or goat manure did not affect the density of Oribatida, whereas the other doses decreased it, but only the highest doses decreased it significantly, compared to the control. Species diversity decreased with the dose of manure. In total, 24 species of Oribatida were found and some species reacted differently to both types of manure. For example, a low dose of pig manure significantly increased the density of Eupelops occultus, whereas the density of other species significantly decreased under the influence of the highest dose of pig manure (Achipteria coleoptrata), highest doses of pig and goat manure (Galumna obvia, Liebstadia similis), and medium and highest doses of goat manure (Scheloribates laevigatus).